Building of a radioactive two‐phase mixing prototype for the evaluation of extrinsic correction maps in spect gamma cameras - Velásquez, María (2017)
Proper operation of the hardware and software of a SPECT Gamma Camera depends on its correct configuration and quality control. These are essential to obtain clinically valid images. In spite of the fact that these are recommended by the equipment manufacturer, these operations are not described in the manuals. The objective of the present work is to propose a unique method for the extrinsic quality control of any SPECT Gamma Camera manufactured to NEMA – IEC specifications. For this purpose, an automatic mixing module has been built to prepare uniform field phantoms, so as to carry out the quality control of the SPECT equipment. The module consists of an automatic mixer and a dummy (phantom). Thanks to the homogeneity of two‐ phase mixtures, we can obtain extrinsic correction maps which will serve to evaluate the quality of the equipment. This operation depends upon the homogeneity of the mixture and its optimal distribution in the phantom and in precise quantities, such as: sodium chloride 0.9% (3.5 liters) and sodium pertechnetate Tc 99m (?20mCi) from 0.1 to 0.4 ml. Radiation exposure must also be considered while preparing the mixture and trying to obtain an adequate dilution of a small amount of Tc‐99m in the volume of distilled water contained in the dummy in the shortest possible time. Analysis of the performance of the mixing module has been a very important research work. This depends upon an appropriate design of the mixing system: geometry of the impeller, mathematical modelling of the mixture, measurement of concentrations, various tests (geometry of the container, volume, diameter), speed and power of the motor, shape of the mixing blades (angle and number), all being important components to reach our objectives. The efficiency of the two‐phase mixture has been demonstrated when the SPECT Gamma Camera currently used by the INEN Nuclear Medicine Center obtained images of optimal quality.